Nursing strategy for patients with atrial fibrillation and heart failure (心房颤动合并心力衰竭患者的护理对策) - LIANG Feng (梁凤); LONG Jie (龙杰); DONG Baoli (董宝丽); SONG Shulan (宋姝斓); LAO Xiaoqing (劳小清); DIAO Guangying (刁光莹) (中西医结合护理)
Atrial fibrillation combined with heart failure is a cardiovascular disease, which seriously threatening the life and health of patients. This paper reviewed studies on nursing strategy for patients with atrial fibrillation and heart failure in perspectives of illness condition, fluid management, diet nursing, medication care, psychological care, nursing cooperation with catheter ablation, rehabilitation exercise, and provided reference for clinical practice. (心房颤动合并心力衰竭是严重的心血管疾病, 严重威胁患者的生命健康。本研究从病情观察、容量管理、饮食护理、用药护理、心理护理、导管消融护理、运动康复训练护理等方面总结心房颤动伴心力衰竭患者的护理进展, 旨在为临床护理工作提供参考。)